Pengembangan Media Pembelajaran Materi Segi Empat Menggunakan Aplikasi Smart Apps Creator Untuk Siswa Sekolah Dasar Kelas IV - Reska Madila Fitri; Yullys Helsa (LPPM Politeknik Pratama, 2024)
This research was motivated by elementary school teachers generally teaching using the lecture method and rarely using learning media so that students only focus on listening to the teacher's explanation. This research aims to produce the development of learning media for quadrangular material using the Smart Apps Creator application for grade IV elementary school students that is valid, practical and effective. This type of research is research and development based on Smart Apps Creator using the ADDIE model with stages of analysis, design, development, application and evaluation. The data collection instruments in this study are validation instruments, practicality and effectiveness instruments. The steps of analyzing data are data analysis of validity, practicality and effectiveness. The development of the results of this research with the ADDIE development model using the Smart Apps Creator Application for Grade IV Elementary School students obtained an average result from three expert validators of 95.66% with a very valid category. The Smart Apps Creator application is very practical to use by obtaining teacher response results of 97.5% with a very practical category and student response results with a percentage of 91.55% with a very practical category. The Smart Apps Creator application is effectively used in the learning process with the results of the effectiveness test at the first meeting obtained a percentage of learning outcomes of 91.36%. Then at the second meeting, the percentage of learning outcomes increased by 96.13%.